Addressing Emotional Intelligence and Socio-Emotional Learning Gaps for Delivery Gig Workers in Chennai, Tamil Nadu: A Response to the Growing Gig Economy - Arumugam, Sandhanakumari (Digital Repository of Theses, 2026)
The study investigates the effect of Emotional Intelligence (EI) and Socio-Emotional Learning (SEL) programs on delivery workers' job satisfaction, emotional resilience, and customer service. Theoretical frameworks of EI and Self-Determination Theory guided the main research through advancing the understanding of socio-emotional issues using stress management, empathy, and self-regulation skills. The literature review offers a rigorous critique of the Western countries' gig economy growth and, at the same time, exposes the specific issues of delivery staff, such as gender-specific vulnerabilities and no informal emotional support. The gap in existing studies largely relates to the knowledge of the role that EI and SEL models play in the development of workers' well-being and thus the need for specific practitioner-oriented interventions. The mixed-methods research design was employed in the present study, comprising quantitative surveys and qualitative content analysis. To evaluate the dimensions of job satisfaction, stress, and emotional resilience, the quantitative data were gathered from a sample of 100 delivery workers and 200 consumers in Chennai, which were then subjected to descriptive and inferential statistical analyses. Qualitative insights were generated through the systematic content analysis of six secondary research papers selected for focusing on the gig economy worker experiences, emotional strains, and service performance. The findings showed that emotional intelligence, especially self-regulation and empathy, was positively linked to better job satisfaction and stronger coping skills among the delivery workers. The customers also identified emotionally intelligent workers as being the ones with high-quality service and good communication. Besides, the content analysis corroborated these results, indicating the emotional difficulties and the absence of a support structure throughout the industry. The study concludes that embedding mobile-first, context-sensitive EI and SEL learning programs into delivery platforms can foster psychosocial well-being and operational sustainability. These findings highlight the need for policy and platform-level reforms that prioritize emotional development alongside efficiency metrics. Keywords: Gig Economy, Emotional Intelligence, Social-Emotional Learning, Delivery Partners, Gig Workers, Chennai.